THE IDEOLOGICAL CONFLICT OF GENERAL SOEMITRO AND ALI MOERTOPO IN THE MILITARY BODY, 1971-1974 - Nuralfia, Siti (Universitas Negeri Yogyakarta, 2023)
Abstract- The conflict between General Soemitro and General Ali Moertopo was a part of the internal army conflict that occurred around 1971-1974. Ideological differences gave rise to dualism within the military between General Soemitro (liberal ideology) and General Ali Moertopo (machiavellis). The rivalry between Soemitro and Ali Moertopo began when President Soeharto, during the early days of his reign, focused on economic recovery as well as strengthening his control over the armed forces. The realization was that institutions such as kopkamtib, special opsus, and Aspri (personal assistant) were established which aimed at maintaining government stability. This government program opened up opportunities for the interests of Ali Moertopo, Soemitro and other military elites to enter. The research aims to examine in depth the ideological conflict that occurred between General Soemitro and General Ali Moertopo 1971-1974. This study uses historical research methods, through heuristic, criticism, interpretation, and historiography stages using a politicological approach and borrowing Collins' conflict theory. The results showed that the conflict related to ideological issues was caused by different views regarding the professionalism of ABRI and rivalry within the military..Keywords: General Soemitro, General Ali Moertopo, Ideological Conflict